Alcohol Detection and Engine Cut-Off System using MQ-3 Sensor with GPS and Telegram Alert - Rahimi, Muhammad Fikri; Lias, Jais (Evolution in Electrical and Electronic Engineering, 2025)
This project is proposed to enhance road safety by preventing drunk driving via an automated method. The proposed method detects alcohol on the driver’s breath using an alcohol sensor, a GPS module, a Telegram notification, and a microcontroller (ESP32). When the system detects the issue, it cuts off the vehicle’s engine and transmits real-time notifications with position information to chosen contacts. The process includes designing and integrating hardware components, programming the microcontroller for alcohol detection, and implementing GPS tracking and Telegram alert integration. Testing happens in controlled situations to confirm the performance and dependability of the alcohol detecting system, engine lock, GPS accuracy, and Telegram notifications. The findings show that the system successfully prevents vehicle operation while under the influence of alcohol and provides timely notifications, guaranteeing increased safety for drivers and the public. In conclusion, this project demonstrates that integrating alcohol detection with engine control and communication technologies can be an effective solution to reduce drunk-driving incidents and enhance road safety.